Intraoperative Radiotherapy in the Management of Locally Recurrent Extremity Soft Tissue Sarcoma. (9th August 2015) - Tinkle, Christopher L.; Weinberg, Vivian; Braunstein, Steve E.; Wustrack, Rosanna; Horvai, Andrew; Jahan, Thierry; O'Donnell, Richard J.; Gottschalk, Alexander R.
Abstract : Purpose . To investigate the efficacy and morbidity of limb-sparing surgery with intraoperative radiotherapy (IORT) for patients with locally recurrent extremity soft tissue sarcoma (ESTS). Methods and Materials . Twenty-six consecutively treated patients were identified in a single institution retrospective analysis of patients with locally recurrent ESTS treated with IORT following salvage limb-sparing resection from May 2000 to July 2011. Fifteen (58%) patients received external beam radiotherapy (EBRT) prior to recurrence (median dose 63 Gy), while 11 (42%) patients received EBRT following IORT (median dose 52 Gy). The Kaplan-Meier product limit method was used to estimate disease control and survival and subsets were compared using a log rank statistic, Cox's regression model was used to determine independent predictors of disease outcome, and toxicity was reported according to CTCAE v4.0 guidelines. Results . With a median duration of follow-up from surgery and IORT of 34.9 months (range: 4 to 139 mos.), 10 patients developed a local recurrence with 4 subsequently undergoing amputation. The 5-year estimate for local control (LC) was 58% (95% CI: 36–75%), for amputation-free was 81% (95% CI: 57–93%), for metastasis-free control (MFC) was 56% (95% CI: 31–75%), for disease-free survival (DFS) was 35% (95% CI: 17–54%), and for overall survival (OS) was 50% (95% CI: 24–71%). Prior EBRT did not appear to influence disease control (LC, p = 0.74 ; MFC, p = 0.66 ) or survival (DFS, p = 0.16 ; OS, p = 0.58 ). Grade 3 or higher acute and late toxicities were reported for 6 (23%) and 8 (31%) patients, respectively. The frequency of both acute and late grade 3 or higher toxicities occurred equally between patients who received EBRT prior to or after IORT. Conclusions . IORT in combination with oncologic resection of recurrent ESTS yields good rates of local control and limb-salvage with acceptable morbidity. Within the limitations of small subsets, these data suggest that prior EBRT does not significantly influence disease control or toxicity.